Volume 1: Aircraft Engine; Marine; Turbomachinery; Microturbines and Small Turbomachinery 2001
DOI: 10.1115/2001-gt-0307
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady Aerodynamical Blade Row Interaction in a New Multistage Research Turbine: Part 2 — Numerical Investigation

Abstract: This paper is the second part of a two part paper, which describes in part one the experimental setup and results of a new multistage turbine. Part two presents results of unsteady viscous flow calculations based on cold flow experiments of that three stage low pressure turbine. The present paper emphasizes the investigation of stator-stator interaction of a low pressure turbine section of a commercial jet engine. Different positions for the second and third stator are studied numerically and experimentally wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Binder et al [6], studied the effect of the turbulence level in a rotor row created by the preceding rotor wakes migrating across the intermediate stator. It is generally assumed that clocking is a potential mean to control the boundary layer transition in LP turbines and to improve efficiency (Gombert and Hohn [7]; Hohn et al [8]). However, Arnone et al [9] concluded that, because of the three-dimensional environment (geometry and flow), the not-perfect alignment between the first stator wakes and the second stator leading edges over the entire radius is difficult to achieve and the clocking effects are reduced.…”
Section: Introductionmentioning
confidence: 99%
“…Binder et al [6], studied the effect of the turbulence level in a rotor row created by the preceding rotor wakes migrating across the intermediate stator. It is generally assumed that clocking is a potential mean to control the boundary layer transition in LP turbines and to improve efficiency (Gombert and Hohn [7]; Hohn et al [8]). However, Arnone et al [9] concluded that, because of the three-dimensional environment (geometry and flow), the not-perfect alignment between the first stator wakes and the second stator leading edges over the entire radius is difficult to achieve and the clocking effects are reduced.…”
Section: Introductionmentioning
confidence: 99%